Appropriation and Scholarly Plagiarism. A Case Study on a Female Student Beginning at Writing in Higher School - Vargas-Franco, Alfonso (Íkala, Revista de Lenguaje y Cultura, 2019)
This paper aims at describing and analyzing the beliefs, views, and feelings of a student concerning academic plagiarism, in which she incurred when working on a reflection article in a teacher training program. Despite its importance in academic writing, this phenomenon has been little explored in the research on writing in higher education in Colombia. This qualitative research study, designed as a case study, within the framework of academic literacies, shows that incurring in this practice may occur, not as a willful act of bad faith, but due to other factors such as lack of experience on the part of the writer, “appropriation” by the teach-er, a pair or an adult, as well as lack of criteria to properly apply citation rules and intertextual practices, as required when writing papers and, more notably, because of the pressure to get a good grade, etc. Otherwise said, this is a mistake regarding the application of academic writing rules. Among others, we conclude that plagiarism requires not only a punitive approach, but more diverse and di-dactic measures, incorporating, on the one hand, the use of extensive writing and learning strategies in the classroom, and, on the other hand, theories and models for citation, and intertextuality as central elements in academic texts.